Associação entre vitamina D e função endotelial em uma subamostra de participantes do Estudo Longitudinal da Saúde do Adulto (ELSA – BRASIL). - Maira Cândida Rodrigues de Sousa (2021)
The Longitudinal Study of Adult Health (ELSA - BRASIL) is a multicentric and multidisciplinary cohort study aimed at investigating the incidence and risk factors of chronic diseases such as cardiovascular disease, diabetes, and obesity. Vitamin D has an important systemic function through its regulatory, anti-inflammatory, and antithrombotic actions and, therefore, its deficiency has been associated with several comorbidities. It is known that there is a probable association between vitamin D and endothelial function through the renin-angiotensin system, by promoting the availability of nitric oxide and by immunomodulation. In this context, the need to assess the impact of vitamin D on endothelial dysfunction in a large-scale study is justified. Thus, in this study, serum levels of vitamin D were determined in 509 participants of the ELSA - BRASIL, CI-MG and its association with sociodemographic, clinical, and endothelial function parameters by Peripheral Arterial Tonometry (BPA and PATratio). These data were provided by the ELSA – Brazil / CI-MG database and vitamin D levels were determined by high performance liquid chromatography (HPLC). No association was observed between vitamin D levels and the sociodemographic, behavioral, and clinical characteristics of the participants. Nevertheless, reduced levels of vitamin D were shown to be associated with indicative measures of worse endothelial function. In the logistic regression model, the variables male gender, non-white color, increase in age, BMI, triglycerides, and vitamin D <30ng/mL were also indicative of worse endothelial function. While the increase in serum HDLc and vitamin D concentrations were indicative of a better endothelial function. In summary, vitamin D has presented an association with endothelial function, which may indicate a protective action of the vitamin in favor of the vascular endothelium.